2022
DOI: 10.1155/2022/2482728
|View full text |Cite|
|
Sign up to set email alerts
|

Study on the Influencing Factors of Osteoarthritis in Southern China

Abstract: Background. Osteoarthritis (OA) is a common chronic disease with numerous and interacting influencing factors, and current inadequate patient perceptions and behaviors in access to care contribute to the difficulties in the diagnosis, treatment, and management of osteoarthritis. Objective. The purpose of this study was to investigate the influencing factors of osteoarthritis (OA) in a southern Chinese population and to provide a scientific basis for the prevention and treatment of OA. Methods. A 1 : 2 matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The results of the period effect in this study show that the period RR of osteoarthritis incidence and DALY rates kept increasing in the cohort born before 2005–2009, and then, it was gradually reduced by year of birth in the cohort born after 2005–2009. The possible reason is that after 2005–2009, through extensive health education [ 36 ]and the emergence of new treatment methods [ 37 39 ] in recent years, the incidence and DALY rate of osteoarthritis will be reduced. The cohort effect refers to the risk of exposure to different levels of social, natural, and environmental factors, depending on the age of birth of the population.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the period effect in this study show that the period RR of osteoarthritis incidence and DALY rates kept increasing in the cohort born before 2005–2009, and then, it was gradually reduced by year of birth in the cohort born after 2005–2009. The possible reason is that after 2005–2009, through extensive health education [ 36 ]and the emergence of new treatment methods [ 37 39 ] in recent years, the incidence and DALY rate of osteoarthritis will be reduced. The cohort effect refers to the risk of exposure to different levels of social, natural, and environmental factors, depending on the age of birth of the population.…”
Section: Discussionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%